What makes sense? Searching for strong WSD predictors in Croatian - Bakarić, Nikola (Array, 2007)
The goal of this research was to investigate and determine position of strong predictors for word sense disambiguation of Croatian nouns. // Research was conducted using supervised learning methods and a corpus of around 70 million words. We have concluded that words in the immediate vicinity of an observed lexeme (1-5 words left and right) have the highest discriminative power. We have also measured the applicability and accuracy of the one-sense- per-discourse method and found it to be very successful as well as the impact of sentence boundaries which proved not to be a good criterion for selecting strong predictors.